Potensi Asap Cair dari Kayu Bengkirai dalam Menghambat Pertumbuhan Jamur Schizophyllum commune Secara In Vitro - Dediwanto, Yordanus; Oramahi, Hasan Ashari; Nurhaida, N (Journal Galung Tropika, 2020)
The activity test of liquid smoke obtained from bengkirai wood (Shorea leavis Ridl)against Schizophyllum commune was evaluated. Two types of liquid smoke from bengkirai wood (Shorea leavis Ridl) was produced at 350° and 450°C. This study aims to evaluate the antifungal properties of liquid smoke from bengkirai wood in inhibiting the growth of S. commune in vitro. Potato dextrose agar (PDA) medium for the efficacy of the liquid smoke of bengkirai wood on the growth of S. commune fungus. Efficacy of liquid smoke of bengkirai wood against S. commune with a completely randomized factorial design, namely temperature pyrolysis of liquid smoke (350° and 450°C) and concentration of liquid smoke (0%, 0.5%, 1.0% and 1.5%, v/v). The results showed that liquid smoked produced at 350° and 450°C exhibited thorough inhibition of growth of S. commune at 1.5%.